NEOLOGISME MENGGUNAKAN AKRONIM DAN ABREVIASI DALAM DOTA 2 - Aji, Willy (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2018)
Every human being in this world certainly uses a language as communication. In this modern era, there are so many media that provide the means to communicate each other. Itâ€™s through social networks such as Facebook or Twitter, or using a cell phone that at this moment there are so many softwares for chatting and SMS. With the Internet in this modern era, the development of language increase rapidly. The created of a new word and language makes the language more variety. Same is in the online games that are widespread recently, thatâ€™s easy to find a new words and languages in online games. But not least people do not understand the definition that word. In this research entitled â€œNeologism using acronyms and abbreviations in DOTA 2â€ will discusses about the formations of words or meanings using neologism theory in DOTA 2. DOTA 2 is a multiplayer online game that developed by Valve company. There are a lot of new words using the form acronym and abbreviation. This phenomenon is very interesting to discuss in this article because that new language not only used in the game but also used in daily activity by gamer.